2013
DOI: 10.1002/wrna.1178
|View full text |Cite
|
Sign up to set email alerts
|

Alternative RNA splicing and cancer

Abstract: Alternative splicing of pre-messenger RNA (mRNA) is a fundamental mechanism by which a gene can give rise to multiple distinct mRNA transcripts, yielding protein isoforms with different, even opposing, functions. With the recognition that alternative splicing occurs in nearly all human genes, its relationship with cancer-associated pathways has emerged as a rapidly growing field. In this review, we summarize recent findings that have implicated the critical role of alternative splicing in cancer and discuss cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 226 publications
(271 reference statements)
0
74
0
1
Order By: Relevance
“…Furthermore, since regulatory and signaling elements in disordered regions can be comprised of just a few more or less continuous amino acids, and since a high density of functionally important segments can be located within disordered regions, functionality of IDPs can be completely rewired via AS. 266,267 AS is known to occur in almost all human genes, and therefore alterations of this process are intimately connected to the pathogenesis of various human diseases, ranging from cancer, 268,269 to neurodegenerative [270][271][272] and cardiovascular diseases. 273 Many of the pathology-related proteins affected by pathology-related AS are intrinsically disordered.…”
Section: Alternative Splicing In Idp Function and Dysfunctionmentioning
confidence: 99%
“…Furthermore, since regulatory and signaling elements in disordered regions can be comprised of just a few more or less continuous amino acids, and since a high density of functionally important segments can be located within disordered regions, functionality of IDPs can be completely rewired via AS. 266,267 AS is known to occur in almost all human genes, and therefore alterations of this process are intimately connected to the pathogenesis of various human diseases, ranging from cancer, 268,269 to neurodegenerative [270][271][272] and cardiovascular diseases. 273 Many of the pathology-related proteins affected by pathology-related AS are intrinsically disordered.…”
Section: Alternative Splicing In Idp Function and Dysfunctionmentioning
confidence: 99%
“…RNA splicing, the process from nuclear pre-mRNA into mature mRNA where introns are excised and the exons (coding regions) are joined together is mediated by a large complex, called spliceosome or spliceosomal machinery (32,33). In human genome, 60% of the mature mRNAs are spliced by alternative splicing in which pre-mRNAs can be spliced in more than one way (34,35). Alternative splicing tremendously increases the diversity of human transcriptome, resulting in translation of more complex proteome in human.…”
Section: The Spliceosomal Machinery and Rna Splicing Regulationmentioning
confidence: 99%
“…The aberrant activation of EMT can be driven by a family of transcription factors, such as the Snail-or Twist-family proteins, and by the cytokine TGFÎČ. Recent work from our lab has demonstrated that EMT is controlled at the level of alternative RNA splicing, a mechanism that is essential to generate protein diversity (Brown et al, 2011;Liu and Cheng, 2013;Xu et al, 2014). These studies relied on analysis of a crucial cell surface molecule, CD44.…”
Section: Introductionmentioning
confidence: 99%